A Review of Clinical Disease Scoring Systems for Cicatricial Diseases of the Conjunctiva - Ong, Hon Shing; Dart, John K.; Mehta, Jodhbir S. (Frontiers in Medicine, 2021)
Cicatricial conjunctival diseases (CCDs), are a diverse group of ocular surface diseases characterised by chronic scarring of the conjunctiva. These diseases can cause significant ocular morbidity. They are life-long once acquired and can be debilitating, painful diseases leading to visual loss. A recent international consensus of ocular surface disease experts have placed emphasis on the need of validated clinical disease scoring systems for CCDs, important for the objective evaluation of disease severity, outcomes of therapies, and longitudinal monitoring of disease. This review aims to describe the various published clinical disease scoring systems available for CCDs and evaluates the benefits and limitations of each system. It can be used as a guide for clinicians managing patients with CCDs and for researchers evaluating potential therapies in clinical trials.